Model-Model Kehidupan Menggereja dalam Terang Ensiklik Fratelli Tutti - Laike, Renold Aleksander (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2021)
In his encyclical, Fratelli Tutti, Pope Francis invites everyone to move beyond his or her own world and open to others in the pursuit of universal fraternity and social friendship. However, the seeds of division are also growing in the Church’s internal environment today. In the life of the Church, there have been rifts in various levels of fraternal relation, which is often triggered by the tendency of some members in prioritising personal or group interests. This tendency can create barriers that hinder the growth and the development of healthy relationships in Christian life and may affect the pastoral care in the field. This article responds to these problems by offering some models to (re)build the fraternity in the Church by delving into the spirituality inspired by Fratelli Tutti. The models bring forward themes like generosity without borders, all-embracing dialogue, and new encounters. From their methodological characters, these models are basically flexible, open to interpretation according to the contextual challenges, and complement to each other. The approaches of these models are intended to realise the spirituality of fraternity from among the Church members.